Risk Identification And Risk Analysis Effects On BMT Financial Performance With Islamic Corporate Governance as A Moderator - Sari, Yuli Indah; Widhyasti, Sasti Anjana; Bakti, Ilham Teruna; Hapsari, Vinandri; Riyadi, Sugeng (Badan Penerbit Universitas Muria Kudus, 2026)
The role of Islamic financial institutions has been confirmed as crucial in supporting Indonesia's economic growth, especially in improving the welfare of micro-communities through providing easy access to financing. However, in the current era of digitisation, Islamic finance faces potential threats related to operational closures due to an inadequate handling of risks. Thus, the purpose of this study is to investigate how risk identification and analysis affect financial performance as well as how Islamic corporate governance (ICG) influences the impact of risk management on financial performance. BMT Bina Umat Sejahtera is the subject of the study. Purposive sampling and the Slovin method were employed as the sampling techniques, and a total of 105 respondents were successfully recruited. The research findings indicate that financial performance is significantly improved by risk detection and analysis. Meanwhile, ICG is not a moderating variable as it does not have a significant effect. The practical implications for the Islamic financial industry emphasise the importance of risk identification and analysis, as well as the development of ICG to strengthen its role in enhancing financial performance. Keywords: Risk Identification, Risk Analysis, Corporate Governance, Financial Performance